Application of the Lagrange multiplier method in finding the conditional extremum of a function of two variables - Chay, Zoya; Rakhimova, Feruza; Islamova, Odila (MMIT Proceedings, 2025)
From many years of experience it is known that students find it difficult to calculate the conditional extremum of functions of several variables. This article discusses the Lagrange method for calculating the conditional extremum. One example is given and solved. A program for calculating the conditional extremum using the Lagrange method has been compiled and the program result is presented.